2010
DOI: 10.1117/12.842987
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of hard tissue ablation by forward-viewing optical coherence tomography

Abstract: A key issue in laser surgery is the inability for the human operator to stop the laser irradiation in time while cutting/ablating delicate tissue layers. In the present work, we forward-image through the laser machining front in complex biological tissue (dense bovine bone) to monitor the incision's approach to subsurface interfaces in real-time (47-312 kHz line rate). Feedback from imaging is used to stop the drilling process within 150 microns of a targeted interface. This is accomplished by combining the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, ICI is not blinded by intense backscatter from the machining laser or plasma light created from ablation due to its highly selective spatial, wavelength, and coherent filtering. In previous work, we demonstrated that ICI can be used to measure key parameters for process development such as etch rate and morphology relaxation in industrial materials and bone 16, 17. In the present work using a second generation system (with a lower cost and higher speed camera), ICI is tested with different laser sources that achieve ablation in hard tissue through very different mechanisms (thermal and ultrashort pulsed regimes).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, ICI is not blinded by intense backscatter from the machining laser or plasma light created from ablation due to its highly selective spatial, wavelength, and coherent filtering. In previous work, we demonstrated that ICI can be used to measure key parameters for process development such as etch rate and morphology relaxation in industrial materials and bone 16, 17. In the present work using a second generation system (with a lower cost and higher speed camera), ICI is tested with different laser sources that achieve ablation in hard tissue through very different mechanisms (thermal and ultrashort pulsed regimes).…”
Section: Introductionmentioning
confidence: 95%
“…With acquisition rates of even a few tens of kilohertz, M-mode images are not only able to directly measure etch rates 13,14 but also melt pool flow 11 and other dynamics of laser drilling processes. 15 Since sensing below the machining front is possible, M-mode data can also be used to guide blind hole cutting in a variety of semitransparent materials including biological tissue 16 even when the exact sample geometry is not known a priori.…”
Section: Introductionmentioning
confidence: 99%